Pengalaman Hidup Pasien Chronic Kidney Disease yang Menjalani Hemodialisis: Scoping Review - Rahmah, Tira Nur; Pujikurniawati, Citra Reza; Hendriyani, Desy; Handayani, Meyla Sari; Wahyuni, Hera; Sridiawati, Essy; Trisyani, Yanny (Universitas Malahayati, 2025)
ABSTRACT Chronic Kidney Disease is a global health problem that occurs every year. Patients can survive by undergoing hemodialysis therapy, but it still leaves a number of important issues as a result of hemodialysis therapy. The purpose of this study was to identify the life experiences of chronic kidney disease patients undergoing hemodialysis. This study used a literature review method with a scoping review approach to explore the experiences of chronic kidney failure patients undergoing hemodialysis. Searches of three databases includes EBSCOhost, PubMed, and Scopus. The keywords used in English were “chronic kidney disease” OR “chronic renal failure” OR “CKD” OR “ESRD” AND “life experiences” OR “lived experiences” AND “during hemodialysis” OR “undergoing hemodialysis”. There were several interrelated themes in exploring the experiences of chronic kidney failure patients undergoing hemodialysis, including emotional and social support, physical and life limitations, psychological impact, economic difficulties, changes in health and knowledge about treatment, and dependence. These findings suggest that the experiences felt by patients with chronic renal failure undergoing hemodialysis are interconnected and have a significant influence on patients' overall quality of life. The implications of these findings suggest that a holistic approach in the care of hemodialysis patients is necessary so that medical interventions cover the physical, emotional, social, and economic aspects of patients. This study provides important insights for healthcare professionals to design more comprehensive and patient-centered interventions. Keywords: Chronic Kidney Disease, Hemodialysis, Life experience ABSTRAK Chronic Kidney Disease adalah masalah kesehatan global yang sering terjadi di setiap tahunnya. Pasien bisa bertahan hidup dengan menjalani terapi hemodialisis, namun masih menyisakan sejumlah persoalan penting sebagai dampak dari terapi hemodialisis. Tujuan penelitian ini adalah untuk mengidentifikasi pengalaman hidup pasien chronic kidney disease yang menjalani hemodialisis. Penelitian ini menggunakan metode literature review dengan pendekatan scoping review untuk mengeksplorasi pengalaman pasien gagal ginjal kronis yang menjalani hemodialisis. Pencarian menggunakan tiga database terdiri dari EBSCOhost, PubMed, dan Scopus. Kata kunci yang digunakan dalam bahasa Inggris yaitu “chronic kidney disease” OR “chronic renal failure” OR “CKD” OR “ESRD” AND “life experiences” OR “lived experience” AND “during hemodialysis” OR “undergoing hemodialysis”. Terdapat beberapa tema yang saling berkaitan satu sama lain dalam mengeksplorasi pengalaman pasien gagal ginjal kronis yang menjalani hemodialisis, diantaranya dukungan emosional dan sosial, keterbatasan fisik dan hidup, dampak psikologis, kesulitan ekonomi, perubahan kesehatan dan pengetahuan tentang perawatan, serta ketergantungan. Temuan ini menunjukkan bahwa pengalaman yang dirasakan oleh pasien dengan gagal ginjal kronis yang menjalani hemodialisis saling berhubungan dan memiliki pengaruh signifikan terhadap kualitas hidup pasien secara keseluruhan. Implikasi dari temuan ini menunjukkan bahwa pendekatan holistik dalam perawatan pasien hemodialisis sangat diperlukan agar intervensi medis mencakup aspek fisik, emosional, sosial, dan ekonomi pasien. Penelitian ini memberikan wawasan penting bagi tenaga kesehatan untuk merancang intervensi yang lebih komprehenif dan berpusat pada pasien. Kata Kunci: Chronic Kidney Disease, Hemodialisis, Pengalaman Hidup